The Acoustic Performance of Natural Composites in Reducing Stress Levels: Textile Industry - Maria P. Widjanarti; Ari Probandari; . Sumardiyono; . Sunarto (Salehan Institute of Higher Education, 2023)
The porous characteristics of recycled natural fibres make them suitable for use as acoustic materials. Straw and water hyacinth fibres are natural materials that can potentially be used as composites in damping devices. This study evaluated the acoustic performance of two types of reinforced composites containing natural fibers (water hyacinth and rice straw) and gypsum adhesives in reducing stress levels in the textile industry. The evaluation was carried out through laboratory tests using impedance tubes and direct testing in a textile factory to reduce the stress level of production machine workers and operators. Rice straw and water hyacinth fibres were thoroughly mixed in proven mass ratios of 10% and 30% with water and gypsum plaster as a binder. The mixture was pressed into a mould at a pressure of 3 MPa before being heated in an oven at 900ºC for 5 hours. Perforations measuring 4 to 8 mm in diameter were then made at equal distances on the panels. Acoustic panel performance tests were carried out with impedance tubes according to ISO 10534-2 standards at sound frequencies ranging from 0 to 6400 Hz. Field tests were also conducted at a textile factory, with each machine unit generating a sound source of 100 to 110 dB. Heart rate data was collected, and noise measurements were carried out before and after the panels were installed in the area around the operating machines. The results showed that the rice straw-gypsum composite with four perforations performed the best, achieving an α coefficient of 1.0 at a frequency of 1500 Hz and an NRC of 0.50, indicating effective noise reduction. The installation of acoustic panels around the noise source in the textile industry reduced noise levels by up to 9.8 dB and was found to affect workers' heart rates, indicating reduced stress levels. The questionnaire results also showed a significant effect on the stress levels of workers. The use of natural fibers in composite materials has the potential to be an eco-friendly and sustainable solution for soundproofing applications. Doi: 10.28991/CEJ-2023-09-06-02 Full Text: PDF